Comparative Analysis Between Fly Ash Geopolymer and Reactive Ultra-Fine Fly Ash Geopolymer - Lin, Wei-Ting; Lin, Kae-Long; Korniejenko, Kinga; Fiala, Lukáš (International Journal of Engineering and Technology Innovation, 2021)
This study investigates novel geopolymers by combining Reactive Ultra-fine Fly Ash (RUFA) with 4M sodium hydroxide as an alkali activator. Comparing with general fly ash geopolymers, RUFA geopolymer pastes are characterized in terms of compressive strength, microstructure, and crystalline phases. The RUFA geopolymer is successfully obtained as alumina-silicate bonding materials with the same properties as the general fly ash-based geopolymer. The high compressive strength of the RUFA-based geopolymer samples (13.33 MPa) can be attributed primarily to Ca-based alumino-silicate hydration products and Na-based alumino-silicate complexes. This research presents an innovative application for geopolymers using RUFA. In the follow-up study, the influence of synthesis and concentration of alkali activator can be considered in RUFA-based geopolymers.